Production of large-transverse-momentum protons - Escobar, C. O. (American Physical Society (APS), 1979)
We discuss in this paper two parton models for the production of large-pT protons. One is the multiple-scattering model of Landshoff, Polkinghorne, and Scott and the other one is the so-called leading-particle model. Several aspects of these models are discussed such as single-particle spectra, event structure, production on nuclear targets, and proton production from pion beams. © 1979 The American Physical Society.